Telenutrition intervention model on changes in knowledge, attitudes, and dietary diversity of toddlers - Perdana, Silvia Mawarti; Muldiasman; Asparian; Aswin, Budi (Proceedings Academic Universitas Jambi, 2025)
Background: Adequate nutrient intake is essential for optimizing growth and development, which supports the nutritional status of children under five years old. Improving parent’s knowledge and attitudes regarding toddler feeding practices, as well as enhancing dietary diversity in toddlers, can be achieved through telenutrition interventions (online nutrition education and consultation) as part of the management of nutritional problems. Objective: This study aimed to analyze changes in knowledge, attitudes, and dietary diversity of toddlers after telenutrition intervention consisting of nutrition education and consultation using the WhatsApp social media platform. Methods: This study employed a quasi-experimental design with one-group pre-test and post-test approach. A total of 53 respondents participated in this study. Nutrition education includes balanced diet for toddlers was delivered through animated videos and flyers, while personal nutrition consultations were conducted using nutrition consultation form to improve toddler’s consumption. Parent’s knowledge and attitudes toward toddler feeding practices were collected through interviews using questionnaires, while dietary diversity data were obtained using the Individual Dietary Diversity Score (IDDS) instrument based on toddler's daily food consumption. Data analysis was performed using the Paired t-test and Wilcoxon test. Results: The study showed that the telenutrition intervention had a significant effect on parent’s knowledge and attitudes toward toddler feeding practices (p < 0.05). However, there was no significant effect of the telenutrition intervention on toddler’s dietary diversity (p > 0.05). Conclusion: Telenutrition intervention can improve parent’s knowledge and attitudes in feeding toddlers by applying the principles of balanced diet.